The inhibition of periodontal ligament stem cells osteogenic differentiation by IL-17 is mediated via MAPKs. (February 2016) - Đorđević, Ivana Okić; Kukolj, Tamara; Krstić, Jelena; Trivanović, Drenka; Obradović, Hristina; Santibañez, Juan F.; Mojsilović, Slavko; Ilić, Vesna; Bugarski, Diana; Jauković, Aleksandra
Abstract: Periodontal disease (PD), a degenerative bacterially induced disease of periodontium, can lead to bone resorption and teeth loss. Development of PD includes a strong inflammatory reaction, which involves multiple immune cells and their secreting factors including interleukin-17 (IL-17), which is not only an important modulator of immune and hematopoietic responses but also affects bone metabolism. In the present study we aimed to determine whether IL-17 affects the regenerative potential of periodontal ligament mesenchymal stem cells (PDLSCs) by investigating its ability to modulate osteogenic differentiation of these cells in vitro along with associated signaling pathways. Our results revealed that IL-17 inhibited both the proliferation and migration of PDLSCs and decreased their osteogenic differentiation by activating ERK1, 2 and JNK mitogen-activated protein kinases. Obtained data suggested that IL-17 might contribute to alveolar bone loss in PD.